"Reading the Mind in the Eyes" in Autistic Adults is Modulated by Valence and Difficulty: An InFoR Study. Issue 2 (15th September 2020) - Baltazar, Matias; Geoffray, Marie‐Maude; Chatham, Christopher; Bouvard, Manuel; Martinez Teruel, Axelle; Monnet, David; Scheid, Isabelle; Murzi, Eleonora; Couffin‐Cadiergues, Sandrine; Umbricht, Daniel; Murtagh, Lorraine; Delorme, Richard; et al.
Abstract : Autism spectrum disorders (ASD) are heterogeneous and complex neurodevelopmental conditions that urgently need reliable and sensitive measures to inform diagnosis properly. The Reading the Mind in the Eyes Task (or Eyes Test from now on) is widely used for this purpose. A recent study showed that subcategories of items of the children version of the Eyes Test could be especially discriminative to distinguish ASD and control children. Here, we analyzed the performance on the Eyes Test of 30 high functioning (IQ > 70) adults with ASD and 29 controls from the InFoR cohort multicentric study, using a Generalized Linear Mixed Model. We found that valence and difficulty modulate the performance on the Eyes Test, with easy and positive items being the most discriminative to distinguish ASD and controls. In particular, we suggest this result might be actionable to discriminate ASD patients from controls in subgroups where their overall scores show less difference with controls. We propose for future research the computation of two additional indexes when using the Eyes Test: the first focusing on the easy and positive items (applying a threshold of 70% of correct responses for these items, above which people are at very low risk of having ASD) and the second focusing on the performance gain from difficult to easy items (with a progression of less than 15% showing high risk of having ASD). Our findings open the possibility for a major change in how the Eyes Test is used to inform diagnosis in ASD. Lay Summary: The Eyes Test is used worldwide to inform autism spectrum disorders (ASD) diagnosis. We show here that ASD and neurotypical adults show the most difference in performance on subgroups of items: ASD adults do not improve as expected when comparing easy and difficult items, and they do not show an improvement for items displaying a positive feeling. We advise clinicians to focus on these comparisons to increase the property of the test to distinguish people with ASD from neurotypical adults.